2020 IEEE Security and Privacy Workshops (SPW) 2020
DOI: 10.1109/spw50608.2020.00032
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Sensor and Actuator Attacks on Power Converters for Electric Vehicles

Abstract: Alleviating range anxiety for electric vehicles (i.e., whether such vehicles can be relied upon to travel long distances in a timely manner) is critical for sustainable transportation. Extremely fast charging (XFC), whereby electric vehicles (EV) can be quickly recharged in the time frame it takes to refuel an internal combustion engine, has been proposed to alleviate this concern. A critical component of these chargers is the efficient and proper operation of power converters that convert AC to DC power and o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The authors of [5] mentioned only briefly the possibility of a denial-of-service attack against the charging communication by emitting noise in its spectrum. And the researchers in [17] focused on the electromagnetic susceptibility of the voltage and current sensors in charging stations.…”
Section: Related Workmentioning
confidence: 99%
“…The authors of [5] mentioned only briefly the possibility of a denial-of-service attack against the charging communication by emitting noise in its spectrum. And the researchers in [17] focused on the electromagnetic susceptibility of the voltage and current sensors in charging stations.…”
Section: Related Workmentioning
confidence: 99%
“…With the increasing reliance on electric vehicles and their integration into the smart grid as an energy buffer, the security of the EV charging infrastructure has developed into an active field of research [14], [3]. Security issues that have been uncovered range from the physical layer of the charging station [2], [15], [8] to vulnerabilities in the software [9], [20], [4]. Researchers have also shown that the payment methods available for vehicle owners lack adequate protection.…”
Section: Related Workmentioning
confidence: 99%
“…A small window size (e.g., k = 4) works well to reduce the noise while maintaining the sensitivity. We have y 0 [n] = 6 18 y[n] + Analysis and Manipulation. Suppose that the injection induces perturbations in the system input by X ′ (t) = X(t)+p(t) (Eq.…”
Section: B Validationmentioning
confidence: 99%
“…However, a main barrier in applying existing attack methods to achieve continuous, realtime control is the lack of the feedback from the victim control system. Many works [3], [4], [5], [6] rely on tuning signals by observing statuses such as the sensor measurements and timing-related signals in the victim system to adjust attack effects. However, such approaches can be limited in attacks that require real-time adversarial control.…”
Section: Introductionmentioning
confidence: 99%